2021
DOI: 10.3389/fendo.2021.705154
|View full text |Cite
|
Sign up to set email alerts
|

Weighted Gene Co-Expression Network Analysis Identifies ANGPTL4 as a Key Regulator in Diabetic Cardiomyopathy via FAK/SIRT3/ROS Pathway in Cardiomyocyte

Abstract: BackgroundDiabetic cardiomyopathy (DbCM) is characterized by initial impairment of left ventricular relaxation followed by contractile dysfunction. Despite intensive research, the exact mechanism remains so far unsolved.MethodsWe constructed weighted gene co-expression network analysis (WGCNA) to screen gene modules that were closely related with DbCM based on the GSE5606 dataset, which contained expression data of the cardiac left ventricle in a rodent model of streptozotocin (STZ)-induced DbCM. Then, the mos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 52 publications
(62 reference statements)
0
11
0
Order By: Relevance
“…ANGPTL4 regulates inflammation, proliferation, lipid metabolism, vessel permeability, and tumor progression. Our previous study has found ANGPTL4 as a key regulator in diabetic cardiomyopathy via FAK/SIRT3/ROS pathway in cardiomyocyte ( Dai et al, 2021 ). ANGPTL4 also stimulates STAT3-mediated iNOS expression and enhances angiogenesis to accelerate wound healing in diabetic mice ( Chong et al, 2014 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…ANGPTL4 regulates inflammation, proliferation, lipid metabolism, vessel permeability, and tumor progression. Our previous study has found ANGPTL4 as a key regulator in diabetic cardiomyopathy via FAK/SIRT3/ROS pathway in cardiomyocyte ( Dai et al, 2021 ). ANGPTL4 also stimulates STAT3-mediated iNOS expression and enhances angiogenesis to accelerate wound healing in diabetic mice ( Chong et al, 2014 ).…”
Section: Resultsmentioning
confidence: 99%
“…Unassigned background genes that belonged to none of the modules were denoted with the grey section. The module eigengenes (MEs) and module significance (MS) were defined as previously described ( Dai et al, 2021 ). We applied the MEs and MS to identify the significant module related to psoriasis.…”
Section: Methodsmentioning
confidence: 99%
“…A recent study by Reichelt et al also predicted that high fructose-induced myocardial TG and glycogen accumulation is attributable to increased Pdk4 38 . Furthermore, Pdk4 was identi ed as a DCM susceptibility gene in a previous WGCNA on diabetic heart 39 .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in a model of sucrose-fed rats, cardiac dysfunction is associated with a decreased SIRT3 protein expression (despite an increase at RNA level) and an increased GCN5L1 (protein and RNA) and mitochondrial protein acetylation [ 11 , 17 ]. Decreased SIRT3 levels are also associated with an increased acetylation of SOD2, and an increased oxidative stress and apoptosis in heart of diabetic mice [ 79 ]. Interestingly, exposure of cardiomyoblasts H9c2 to high glucose concentration decreased SIRT3 [ 78 ] and increased GCN5L1, oxidative stress and autophagy mediated by cytoplasmic Forkhead box O1 (FOXO1) acetylation [ 11 , 76 ].…”
Section: Implication Of Cardiac Acetylation In Metabolic Heart Diseasementioning
confidence: 99%